-
If α, β are the roots of the equation x2 - 5x + 6 = 0, construct a quadratic equation whose roots are
1 , 1 . α β
-
- 6x2 + 5x - 1 = 0
- 6x2 - 5x - 1 = 0
- 6x2 - 5x + 1 = 0
- 6x2 + 5x + 1 = 0
Correct Option: C
As per the given above question , we can say that
Comparing x2 - 5x + 6 = 0 with ax2 - bx + c = 0 , we get
a = 1, b = - 5, c = 6
∴ α + β = | = | = 5 | ||
αβ = | = 6 | |
Now, we are to form an equation whose roots are
, | . | ||
x2 − (sum of roots)x + (Product of roots) = 0
x2 | ![]() | + | ![]() | x + | ![]() | . | ![]() | = 0 | ||||
α | β | α | β |
x2 - | ![]() | ![]() | x + | ![]() | ![]() | = 0 | ||
αβ | αβ |
x2 - | x + | = 0 | ||
6x2 - 5x + 1 = 0
Thus , required equation is 6x2 - 5x + 1 = 0 .